دور القطاع الخاص في دعم التنمية الاقتصادية المحلية، دراسة حالة الجزائر - عابد شريط; جلول ياسين بن الحاج (My University, 2016)
شهد العالم في أواخر القرن العشرين تطورات سياسية واقتصادية واجتماعية، انعكست على دور الدولة، وبالتالي حدث انتقال من نظام حكم محلي تسيطر فيه المجالس المحلية المنتخبة إلى نظام حكم محلي يشارك فيه في تحمل المسؤوليات والسلطات والموارد إلى جانب هذه المجالس القطاع الخاص. لذلك لجأت الحكومات المحلية في العديد من الدول إلى تبني سياسات التحول إلى القطاع الخاص. ونهدف من خلال هذا البحث إلى التعرف على مضمون كل من التنمية الاقتصادية المحلية والقطاع الخاص، والدور الذي يمكن أن يلعبه هذا القطاع في عملية التنمية الاقتصادية على المستوى المحلي في الجزائر. وقد توصلنا إلى أن القطاع الخاص يلعب دورا كبيرا في تحقيق أهداف التنمية الاقتصادية المحلية من خلال زيادة معدلات النشاط الاقتصادي وتوفير فرص عمل للمواطنين المحليين، كما يساهم في تعزيز القدرات التنافسية للاقتصاديات المحلية، وفي رفع كفاءة الخدمات العامة المحلية. Abstract: The world has seen in the late twentieth century political, economic and social developments, reflected on the role of the state, and thus the transmission of local government in which elected local councils controlled by the local government is engaged on the responsibilities, authorities and resources as well as the boards of the private sector system occurred. So it resorted local governments in many countries to adopt privatization policies. And the aim of this research is to identify the content of each of the local economic development and the private sector, and the possible role that the sector plays in economic development at the local level in Algeria. We have reached that the private sector plays a major role in achieving the objectives of local economic development through increased economic activity rates and provide job opportunities for local citizens, and contribute to enhancing the competitiveness of local economies, and in raising the efficiency of local public services
Keywords: القطاع الخاص، التنمية الاقتصادية المحلية، الاقتصاد المحلي، منطقة الشمال الغربي للجزائر، مشروعات التنمية المحلية.